1998
DOI: 10.1080/13590849861916
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Decrease in Plasma omega 3 and omega 6 Fatty Acids During Pregnancy: Time Course and Effects of Dietary Fats and Antioxidant Nutrients

Abstract: As part of a previously reported comprehensive study of the nutritional and environmental factors contributing to oxidative stress during pregnancy, breath ethane, a volatile alkane produced during peroxidation of w 3 fatty acids (FAs), was used as a non-invasive measure of oxidative stress. This study investigates relationships between the plasma concentration of w 3 FAs, breath ethane, nutrient intake and serum concentration of selected antioxidant nutrients. The study design included measurement of breath e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…A single cohort study assessed the association between breath ethane (a marker of oxidative stress) and maternal omega-3 status in a sample of 44 women in the second trimester of pregnancy [32]. There was no correlation between breath ethane concentrations and maternal concentrations of ALA, EPA, DPA, DHA or total omega-3 PUFA (µmol/l) in this study.…”
Section: Breath Ethanementioning
confidence: 62%
See 3 more Smart Citations
“…A single cohort study assessed the association between breath ethane (a marker of oxidative stress) and maternal omega-3 status in a sample of 44 women in the second trimester of pregnancy [32]. There was no correlation between breath ethane concentrations and maternal concentrations of ALA, EPA, DPA, DHA or total omega-3 PUFA (µmol/l) in this study.…”
Section: Breath Ethanementioning
confidence: 62%
“…Oleic acid and vitamin A. One cohort study assessed the association between the dietary intakes of oleic acid and vitamin A and maternal omega-3 DPA status in a sample of 44 women in the second trimester of pregnancy [32].…”
Section: Factors Influencing Maternal Omega-3 Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…Breath pentane is derived from the oxidation of n -3 and n -6 fatty acids which appear to be transferred from mother to fetus during pregnancy ( 62 ) . However, in women in their last trimester, who have smoked during pregnancy, it has been reported that breath ethane was higher than for a control group of non-smokers, and inversely related to serum vitamin C ( 63 ) .…”
Section: Physiological Variations In Breath Compositionmentioning
confidence: 99%